2013
DOI: 10.1111/apt.12574
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: the association between human papillomavirus infection and oesophageal cancer

Abstract: These two authors contributed to this work equally. SUMMARY BackgroundHuman papillomavirus (HPV) infection might be one of the potential risk factors for oesophageal cancer. However, the previous epidemiological findings were heterogeneous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
82
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 81 publications
6
82
3
Order By: Relevance
“…Significant association was observed between HR-HPV infection and esophageal squamous cell carcinoma with a summarized odds ratio of 3.32 (95% CI, 2.26-4.87). According to HR-HPV16, the strength of the association was found to be 3.52 (95% CI, 2.04-6.07) [18]. Though HR-HPV18 was not detected in the present study but studies have reported low prevalence rates in the highly infected regions [19].…”
Section: Discussioncontrasting
confidence: 64%
“…Significant association was observed between HR-HPV infection and esophageal squamous cell carcinoma with a summarized odds ratio of 3.32 (95% CI, 2.26-4.87). According to HR-HPV16, the strength of the association was found to be 3.52 (95% CI, 2.04-6.07) [18]. Though HR-HPV18 was not detected in the present study but studies have reported low prevalence rates in the highly infected regions [19].…”
Section: Discussioncontrasting
confidence: 64%
“…Significant association was observed between HPV infection and esophageal SCC with a summarized odds ratio of 3.32 (95% CI, 2.26-4.87). According to HPV16, the strength of the association was found to be 3.52 (95% CI, 2.04-6.07) [16]. Though HPV18 was not detected in the present study but studies have reported low prevalence rates in the highly infected regions [17].…”
Section: Discussioncontrasting
confidence: 60%
“…Results in this study were consistent with these recent meta-analysis and even with a higher prevalence level in our study because the included cases were testing by PCR method which can improve the HPV 16 positive rate in the case tissues. Furthermore, as Li reported (Li et al, 2014), HPV infection might be disappeared during the development of cancer and this clearance of HPV infection may lead to underestimation of the HPV 16 infection. In other words, the high prevalence of HPV 16 may suggested a relative high overall HPV prevalence in esophageal cancer cases.…”
Section: Discussionmentioning
confidence: 98%
“…With respect to esophageal cancer, studies also reported that HPV 16 was the main HPV type (Yong et al, 2013;Li et al, 2014;Petrick et al, 2014), although there is a controversy on this issue. Meta-analysis conducted by Petrick et al showed that HPV 16 prevalence ranged from 17.3% to 35.9% in esophageal cancer using different detecting method (Petrick et al, 2014).…”
Section: Discussionmentioning
confidence: 99%